The effects of acupressure, laughter yoga, and a mindfulness-based stress reduction program applied to postmenopausal women for menopause symptoms and quality of life - Koca, Hacer U.; Kucukkelepce, Didem S.; Nacar, Gulcin; Cetin, Nurdilan S.; Tashan, Sermin T. (Lippincott Williams & Wilkins, 2024)
Objective: This research was conducted to determine the effects of acupressure, laughter yoga, and a mindfulness-based stress reduction program applied to postmenopausal women for menopause symptoms and quality of life. Methods: A randomized controlled design was used. The study was conducted with a total of 146 women, including 41 acupressure, 31 laughter yoga, 37 mindfulness-based stress reduction, and 37 control group women. The women in the acupressure group were administered acupressure twice a week, which accounted for 16 sessions in total. Women in the laughter yoga and mindfulness-based stress reduction groups received a total of eight sessions of the related intervention, which was performed once a week. Study data were collected using a participant information form, the Menopause Rating Scale (MRS), and the Menopause-Specific Quality of Life Scale (MENQOL). Descriptive statistics, paired-samples t test, chi(2) test, analysis of variance test, and intention to treat analysis were used to analyze the data. Before the intention to treat analysis was performed, the multiple imputation method was employed to deal with missing data. Results: In the study, it was found that there was a decrease in the MRS total score after the intervention in women in all three intervention groups compared to the control group (P < 0.05). In the laughter yoga group, total MRS scores decreased by 3.16 points (P < 0.05). In the acupressure group, total MRS scores decreased by 5.46 points (P < 0.05). In the mindfulness-based stress reduction (MBSR) program group, total MRS scores decreased by 4.65 points (P < 0.05). It was determined that the mean scores of women in the laughter yoga and acupressure groups on all subscales of the MENQOL decreased after the intervention compared to the control group (P < 0.05). The comparison of the MBSR group and the control group showed that there was a decrease only in the psychosocial domain subdimension of the MENQOL (P < 0.05). Conclusions: In conclusion, it was determined that laughter yoga, acupressure, and MBSR could be effective in reducing menopause symptoms and improving quality of life, although findings require further testing in a rigorously controlled study and in a study with only a single prespecified outcome.
Keywords: Acupressure; Laughter yoga; Menopause; Mindfulness